2009
DOI: 10.1177/147323000903700322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Borneol on In Vitro Corneal Permeability and on In Vivo and In Vitro Corneal Toxicity

Abstract: This study examined whether borneol could enhance corneal drug permeability. Model drugs containing either synthetic or natural borneol were co-administered to isolated intact or de-epithelialized rabbit corneas and the apparent permeability coefficients were measured. Draize tests in rabbits and levels of isolated intact rabbit corneal hydration were used to measure in vivo and in vitro toxicity, respectively. Synthetic borneol (0.1%) increased corneal penetration of the lipophilic agents, indomethacin and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…28 mg/kg for 7 days reduced H 2 O 2 -induced DNA damage in hepatocytes and testicular cells, respectively ), suggesting a difference in toxic response between acute and chronic borneol regimens. No significant toxic effects of borneol were observed in mouse oral fibroblasts at concentrations of 18.75-150 lg/mL (Dai et al, 2009), corneal tissue at a concentration of 0.1% (Yang et al, 2009), or in rat thymocytes at a concentration of 5 lg/mL (Cherneva et al, 2012). The doses of natural and synthetic borneol recommended for clinical use are 0.3-0.9 g and 0.15-0.3 g, respectively (State Pharmacopoeia Committee, 2015).…”
Section: Toxicological Profilementioning
confidence: 99%
“…28 mg/kg for 7 days reduced H 2 O 2 -induced DNA damage in hepatocytes and testicular cells, respectively ), suggesting a difference in toxic response between acute and chronic borneol regimens. No significant toxic effects of borneol were observed in mouse oral fibroblasts at concentrations of 18.75-150 lg/mL (Dai et al, 2009), corneal tissue at a concentration of 0.1% (Yang et al, 2009), or in rat thymocytes at a concentration of 5 lg/mL (Cherneva et al, 2012). The doses of natural and synthetic borneol recommended for clinical use are 0.3-0.9 g and 0.15-0.3 g, respectively (State Pharmacopoeia Committee, 2015).…”
Section: Toxicological Profilementioning
confidence: 99%
“…htm, 1998). Many studies have reported that borneol can enhance the absorption, distribution, permeability, and efficacy of other drugs (Mai et al, 2003;Xiao et al, 2007;Cai et al, 2008;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Danshensu as the primary ingredient from aqueous extract of Salvia miltiorrhiza (sovereign in FFDS) has been shown to have pleiotropic activities, such as protection from homocystein induced endothelial dysfunction [38], attenuation of increased endothelial permeability induced by TNF [39], inhibition of platelet aggregation [40], improvement of microcirculation [41], and protection of myocardium from reperfusion injury of the ischemic heart [42]. Borneol (courier in FFDS) as an adjuvant element in the FFDS formula, is believed to play assisting roles in facilitating the delivery of principal component, increasing bioavailability and promoting active compounds penetrating the biological barriers [43][44][45]. Based on the understanding of individual functions of Danshensu and borneol and clinical effect of FFDS on atherosclerosis, we hypothesized that the novel compound DBZ might be effective in inhibiting atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%